2022
DOI: 10.1021/acsinfecdis.1c00355
|View full text |Cite
|
Sign up to set email alerts
|

QSAR Classification Models for Prediction of Hydroxamate Histone Deacetylase Inhibitor Activity against Malaria Parasites

Abstract: Malaria, caused by Plasmodium parasites, results in >400,000 deaths annually. There is no effective vaccine, and new drugs with novel modes of action are needed because of increasing parasite resistance to current antimalarials. Histone deacetylases (HDACs) are epigenetic regulatory enzymes that catalyze post-translational protein deacetylation and are promising malaria drug targets. Here, we describe quantitative structure–activity relationship models to predict the antiplasmodial activity of hydroxamate-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…In silico approaches, through molecular docking, also led to the discovery of a new portfolio of parasite specific HAT inhibitors [ 77 , 117 ] and quantitative structure–activity relationship (QSAR) models have been developed as useful tools for in silico screening of Plasmodium HDAC inhibitors [ 137 ]. However, recent progress has been made in the field of malaria epidrugs in order to overcome potential toxicity issues in the mammalian host.…”
Section: Plasmodium Epigenetic Effectors As a Source Of Ther...mentioning
confidence: 99%
“…In silico approaches, through molecular docking, also led to the discovery of a new portfolio of parasite specific HAT inhibitors [ 77 , 117 ] and quantitative structure–activity relationship (QSAR) models have been developed as useful tools for in silico screening of Plasmodium HDAC inhibitors [ 137 ]. However, recent progress has been made in the field of malaria epidrugs in order to overcome potential toxicity issues in the mammalian host.…”
Section: Plasmodium Epigenetic Effectors As a Source Of Ther...mentioning
confidence: 99%
“…ACS Infectious Diseases is contributing to this joint virtual special issue focused on epigenetics with 11 publications in the form of nine innovative research articles, one Perspective, and one Viewpoint. Not surprisingly, histone deacetylase (HDAC) is the target class with a major presence (four research articles), as HDAC has already shown its therapeutic potential to treat infectious diseases. Also notable is the increase of interest in bromo­domains in protozoa; their potential as novel targets against protozoans-mediated diseases is discussed in a Viewpoint and two articles. , Finally, the characterization of acetyl-CoA synthetase as an interesting target for the development of antiplasmodial drugs, the profiling of epigenetic modulators against hemo­protozoan parasites, and two publications focused on the role of the host , complete the contributions from ACS Infectious Diseases to this virtual special issue. We thank Drs.…”
Section: Acs Infectious Diseasesmentioning
confidence: 99%
“…In recent years, there have been several studies on the subject of QSAR analysis. These studies include research on the prediction of smallmolecule binding to RNA, predicting the transfer of environmental chemicals across the placenta, and the classification of inhibitor activity [9,10].…”
Section: Introductionmentioning
confidence: 99%